2015
DOI: 10.3109/1061186x.2015.1055570
|View full text |Cite
|
Sign up to set email alerts
|

Progress in nanotechnology-based drug carrier in designing of curcumin nanomedicines for cancer therapy: current state-of-the-art

Abstract: Comprehensive pharmacological screening of curcumin (CUR) has given the evidence that it is an excellent naturally occurring therapeutic moiety for cancer. It is very well tolerated with insignificant toxicity even after high doses of oral administration. Irrespective of its better quality as an anticancer agent, therapeutic application of CUR is hampered by its extremely low-aqueous solubility and poor bioavailability, rapid clearance and low-cellular uptake. A simple means of breaking up the restrictive fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 157 publications
0
57
0
Order By: Relevance
“…In particular, drug delivery via colloid carrier systems, including liposomes, nanoemulsions, and nanoparticles [23], has become a pharmacological research focus. Like biomembranes, liposomes are composed of lipid membranes, including phospholipids and cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, drug delivery via colloid carrier systems, including liposomes, nanoemulsions, and nanoparticles [23], has become a pharmacological research focus. Like biomembranes, liposomes are composed of lipid membranes, including phospholipids and cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer cell lines, CUR protects against chemoresistance in human gastric cancer cell lines (SGC7901 cells) by down-regulating NF-kB and subsequent NF-kB-mediated anti-apoptotic genes, such as Bcl-2 and Bcl-xL (Chung et al, 2013). It has been also reported that CUR suppresses the expression of epidermal growth factor receptor (EGFR) and was capable of suppressing cell proliferation and migration through inhibition of STAT3 phosphorylation, which contributes to gastric carcinogenesis (Uehara et al, 2014;Ahmad et al, 2015). In spite of excellent therapeutic potential, low-aqueous solubility and rapid systemic elimination limit its application in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin can be used extensively to treat a variety of solid tumors, including stomach, breast and colorectal carcinoma (Cui et al, 2006;Ahmad et al, 2015;Da et al, 2015). In gastric cancer cell lines, CUR protects against chemoresistance in human gastric cancer cell lines (SGC7901 cells) by down-regulating NF-kB and subsequent NF-kB-mediated anti-apoptotic genes, such as Bcl-2 and Bcl-xL (Chung et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Furthermore, these NPs can be utilized for targeted delivery of drugs to improve bioavailability, to sustain drug in target tissues, and to improve the stability of therapeutic agents. 31,32 Properties of the NPs are largely dependent on the polymer employed. 33 Among these polymeric NPs, chitosan (CS)-based nanocarriers have received much attention as a drug delivery system.…”
Section: Introductionmentioning
confidence: 99%